Distance teaching at the tertiary level - Baldo, Trinidad C. (Education quarterly.)
The possibilities of distance teaching are many and varied. At the tertiary level, it is in the area of professional training and retraining where distance teaching has much to offer. Education authorities concerned are therefore expected to seriously consider now the utilization of distance teaching scheme. There is also an urgent need to create a national body which will oversee existing distance teaching programs of the Ministry of Education and Culture as well as those of other institutions. This body will have for its primary function supervision of distance teaching in the country in order to ensure quality instruction at all times.